Effect of temperature and residence time on the characteristics of torrefied food - Abdul Rahman, R. N. U.; Ruwaida, A. R.; Ismail, M. (IOP Publishing Ltd, 2019)
Malaysia generated food waste (FW) is approximately 15 000 tons every day and expected to increase every year. Currently, Malaysia is applying the landfilling method to dispose all of the MSW which cause potential threat towards the environment and society. FW may be converted into more valuable products through reutilizing as a renewable energy source through torrefaction. The objective of this study is to investigate the effect of torrefaction temperature and residence time towards the characteristics of torrefied FW. The torrefaction process was carried out in a fixed bed reactor with continuous flow of nitrogen, at various torrefaction temperature (260 to 320 °C) and residence time (15 to 60 minutes). The torrefied FW was evaluated in terms of its mass yield, thermal behaviour and the produced functional groups through the Fourier transform infrared spectroscopy (FTIR). It can be observed that the higher the torrefaction temperature and residence time reduces the mass yield. Meanwhile, the FTIR spectra for raw and torrefied FW at different residence time was executed the functional group of C=C, C=O, C-O and C-H were present in sample. From this study, it is established that there were significant effects of both parameters towards the characteristic of FW.